Photon region and shadow of a rotating 5D black string - Tang, Zi-Yu; Kuang, Xiao-Mei; Wang, Bin; Qian, Wei-Liang [UNESP] (Springer Nature, 2023)
To explore the possible clues for the extra dimension from the Event Horizon Telescope (EHT) observations, we study the shadow of the rotating 5D black string in General Relativity (GR). Instead of investigating the shadow in the effective 4D theory, we concern the motion of photons along the extra dimension z with a conserved momentum Pz , which appears as an effective mass in the geodesic equations of photons. The existence of Pz enlarges the photon regions and the shadow of the rotating 5D black string while it has slight impact on the distortion. The EHT observations of M87* and SgrA* can rule out the black string model with an infinite length along the extra dimension, and support the hypothesis that the extra dimension is compact to avoid the Gregory-Laflamme (GL) instability, where the length of the black string/the compact extra dimension can be constrained as 2.03125mm≲ℓ≲2.6mm and 2.28070mm≲ℓ≲2.6mm respectively.